Circulating lipocalin 2 is neither related to liver steatosis in patients with non-alcoholic fatty liver disease nor to residual liver function in cirrhosis. (September 2016) - Meier, Elisabeth M.; Pohl, Rebekka; Rein-Fischboeck, Lisa; Schacherer, Doris; Eisinger, Kristina; Wiest, Reiner; Krautbauer, Sabrina; Buechler, Christa
Highlights: Serum lipocalin 2 is not changed in patients with non-alcoholic fatty liver. In alcoholic liver cirrhosis serum lipocalin 2 is not related to liver injury. Hepatic vein, portal vein and systemic lipocalin 2 are comparable. Hepatic vein lipocalin 2 is not related to residual liver function. Abstract: Lipocalin 2 (LCN2) is induced in the injured liver and associated with inflammation. Aim of the present study was to evaluate whether serum LCN2 is a non-invasive marker to assess hepatic steatosis in patients with non-alcoholic fatty liver disease (NAFLD) or residual liver function in patients with liver cirrhosis. Therefore, LCN2 was measured by ELISA in serum of 32 randomly selected patients without fatty liver (controls), 24 patients with ultrasound diagnosed NAFLD and 42 patients with liver cirrhosis mainly due to alcohol. Systemic LCN2 was comparable in patients with liver steatosis, those with liver cirrhosis and controls. LCN2 negatively correlated with bilirubin in both cohorts. In cirrhosis, LCN2 was not associated with more advanced liver injury defined by the CHILD-PUGH score and model for end-stage liver disease score. Resistin but not C-reactive protein or chemerin positively correlated with LCN2. LCN2 levels were not increased in patients with ascites or patients with esophageal varices. Consequently, reduction of portal pressure by transjugular intrahepatic portosystemic shunt did not affect LCN2 levels. Hepatic venous blood (HVS), portal venous blood and systemic venous blood levels of LCN2 were similar. HVS LCN2 was unchanged in patients with end-stage liver cirrhosis compared to those with well-compensated disease arguing against increased hepatic release. Current data exclude that serum LCN2 is of any value as steatosis marker in patients with NAFLD and indicator of liver function in patients with alcoholic liver cirrhosis.